3(e+3f)=

Simple and best practice solution for 3(e+3f)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(e+3f)= equation:


Simplifying
3(e + 3f) = 0
(e * 3 + 3f * 3) = 0
(3e + 9f) = 0

Solving
3e + 9f = 0

Solving for variable 'e'.

Move all terms containing e to the left, all other terms to the right.

Add '-9f' to each side of the equation.
3e + 9f + -9f = 0 + -9f

Combine like terms: 9f + -9f = 0
3e + 0 = 0 + -9f
3e = 0 + -9f
Remove the zero:
3e = -9f

Divide each side by '3'.
e = -3f

Simplifying
e = -3f

See similar equations:

| (6/3+4)= | | x^2-16x+100=36 | | 10.6x+58.54=-9.4x+58 | | X^5-x^4+x^3-x^2= | | 10x+197=2x-187 | | 3x-5y-58=0 | | (5t-3)=3(t+1)+3 | | 3ab^2+6a= | | 7(r)=3.14r^2 | | 3x^2+8=-56 | | -11x+2(3x-5)=-17-4x | | 6(z+8)=5(z-4)+z | | 4cosx-7sinx=0 | | 6(z+8)=6(z-4)+z | | 7n+10=2.5 | | 3x^4+6y^2+6= | | n-44=0 | | 2(20)+9y=1800 | | 5x^3-15x^2-x+3= | | 4(30)+6y=2400 | | 0.09x+x=21800 | | 0.3m+1-1.6m=5 | | 3x+24+58=x+41 | | 3.75m+1-1.6m=5 | | 3x+24+58= | | 3.76m+1-1.6m=5 | | 58+3x+24=x+41 | | 36x=26x | | 58+3x=17 | | 28y+7x=56 | | 7x+28y=56 | | 9x+17=-7 |

Equations solver categories